Selected engineering properties of palmyrah (Borassus flabellifer) leaf base - Kumar, S. Santhosh; Sudagar, I.P.; Rajkumar, P.; Naik, Ravindra; Kavitha, R. (Journal of Plantation Crops, 2021)
Natural fibres are attracting a lot of attention these days, from industrial applications and basic research, to producing eco-friendly goods. The engineering characteristics of the palmyrah leaf base (Borassus flabellifer) were assessed in this study. The test specimen’s were prepared as per the ASTM standards. The average length of the palmyrah leaf base was around 532±0.72 mm, with 22.74±0.23 mm thickness, 472.6±3.23 g density and volume of 0.893±0.027 g cm3 and 173.14±5.393 cm3. The mechanical properties were obtained by tensile test, impact test, flexural test, and shore-D hardness test. Tensile strength was observed to be 8.77 MPa, percentage of elongation was 40 per cent and the flexural strength 147±2.44 MPa. Significant hardness and lower impact strength confirms the viscoelastic nature of the palmyrah leaf base. The data obtained was analysed statistically using Weibull analysis. The palmyrah leaf base properties obtained will be useful for palm related researchers and industrialists to calculate design consideration for fibre extraction machines and developing fibre related products.